Assessing the efficacy of thermotherapy combined with chemotherapy or cryotherapy for the eradication of grapevine leafroll-associated virus 3 - Wante, Solomon Peter; Chooi, Kar Mun; Pathirana, Ranjith; Whibley, Annabel; Bradley, Ellie L.; Liau, Yusmiati; Vanga, Bhanupratap Reddy; Hill, Amy M.; Lizamore, Darrell (Frontiers in Plant Science, 2026)
IntroductionGrapevine leafroll-associated virus 3 (GLRaV-3) poses a significant threat to viticulture and is the major virus pathogen in New Zealand. The presence of the virus is therefore undesirable within the New Zealand Winegrowers National Vine Collection, which serves as a repository of diverse and valuable grapevine genotypes.MethodsThis study evaluated the effectiveness of in vitro virus eradication protocols, specifically thermotherapy combined with chemotherapy (ribavirin or oseltamivir) or cryotherapy, for eliminating GLRaV-3 from infected grapevine cultivars. Virus presence was initially confirmed using enzyme-linked immunosorbent assay (ELISA) and high-throughput sequencing (HTS). Following treatment, plantlets were screened using reverse transcription quantitative polymerase chain reaction (RT-qPCR) for GLRaV-3 detection.ResultsThermotherapy followed by cryotherapy achieved the highest virus elimination rates across cultivars, including complete eradication in Sauvignon Blanc 217, Chenin Blanc, and Riesling Gm 239. Oseltamivir chemotherapy combined with thermotherapy showed higher elimination rates than ribavirin-based treatments, with complete success in Ehrenfelser and Golden Chasselas.DiscussionCultivar-specific responses emphasise the need to optimise treatment protocols to achieve broad efficacy across diverse cultivars. After virus elimination, tissue-cultured material could be maintained in vitro or by cryopreservation for long-term conservation. These findings provide a scalable strategy for restoring high-health status to grapevine cultivars within germplasm repositories, thereby supporting the long-term sustainability of viticulture.